Exploration of Responsive Feeding During Breastfeeding Versus Bottle Feeding of Human Milk: A Within-Subject Pilot Study - Whitfield, Kyly C; Ventura, Alison K (Breastfeeding medicine, 2019)
Responsive feeding promotes optimal feeding patterns and growth trajectories. Breastfeeding is thought to facilitate responsive feeding, but research to date has been limited to comparing formula-feeding and breastfeeding dyads. Using a within-subject approach, we aimed to assess maternal responsiveness to infant cues during two human milk feeding sessions differing by feeding modality (breastfeeding versus bottle feeding). Nine mother-infant dyads (infants ≤6 months) were recruited from the Halifax Regional Municipality, Nova Scotia, from April to May 2018. Two human milk-feeding sessions, directly from the breast and from a bottle, were video-recorded in participants' homes, then scored using the validated Nursing Child Assessment Satellite Training (NCAST) Caregiver/Parent-Child Interaction Feeding Scale. The second half of feeding sessions were coded for infant satiation cues. All women earned a college degree or higher, and were partnered. Mothers were aged mean ± standard deviation 33.2 ± 4.0 years; infants were 14.6 ± 6.9 weeks old and six (67%) were female. Mothers were more sensitive to infant cues during breastfeeding (NCAST Maternal Sensitivity to Cues sub-scale score, 15.0 ± 1.0) than bottle feeding (13.4 ± 1.6; = 0.016). There was a significantly longer latency from feeding session midpoint to the first satiation cue during breastfeeding (minutes:seconds; 3:00 ± 1:53 versus 0:45 ± 1:18 bottle feeding, = 0.038). There was no difference in the number of infant cues by feeding modality. Despite the small sample with high socioeconomic status, this pilot study highlights differences in maternal responsiveness to infant cues by feeding modality with human milk, which warrants further investigation.